PENGEMBANGAN BUKU FISIKA MULTI REPRESENTASI PADA MATERI GELOMBANG DENGAN PENDEKATAN BERBASIS MASALAH - Widya Nurhayati; Vina Serevina; Fauzi Bakri (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
This study aims (1) to develop and produce the physics multiple representationâ€™s book using problem based approach as reference of learning physics of waves, and (2) to describe the advisability of the physics multiple representationâ€™s book using problem based approach by means of validation test. This study has Research and Developmentâ€™s (R & D) method with the modified Dick and Careyâ€™s model. This model was modified by M. Atwi Suparman then become â€œModel Pengembangan Instruksionalâ€ which has the function to develop the modern instructional design. The average percentage of validation test by physics subject expert, media expert, learning expert, and limited test by teacher and student is 85%. As the result, the physics multiple representationâ€™s book using problem based approach is good to be use as physics book. Keywords: Book, Waves, Multiple representations, Problem based approach